Current Studies on the Use of Edmodo in EFL Learning: A Review - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
The growing interest to integrate Edmodo into EFL classroom since its inception about a decade ago has significantly increased studies exploring it as the research area. However, reviews of these studies are still rare. Thus this paper aimed to review 24 current studies focusing on the integration of Edmodo into EFL learning and teaching to draw a general picture of the research designs employed, insights and ideas concerning the adoption of Edmodo in EFL environments, and who were the participants of these studies. The review was conducted using the constant comparative method. The review results showed that (1) the majority of the studies employed designs related to descriptive qualitative methods; (2) research focuses consisted of effects of Edmodo on EFL learning outcomes, impacts of Edmodo towards students’ learning attitude and motivation, perceptions of Edmodo use, and evaluation on Edmodo implementation in EFL learning; and (3) the participants of the study were mainly university students.